Scheme of Community Polytechnics - a Preliminary Evaluation - Planning Commission (Planning Commission, 1983)
The Community Development Programme received due recognition and priority since the advent of the planning era in the country. In the First Five Year Plan, the programme got a fillip with the launching of 52 Community Development Projects on October 2, 1952. Since then, a variety of Community Development Programmes have been sponsored by the Government of India and the State Governments. These programmes meant for the improvement of the conditions of 80 per cent of the country's population living in about 5.67 lakhs of villages have failed to achieve the desired impact on the formidable problem of poverty and unemployment in the rural areas.
Programme Evaluation Organisation Planning Commission Government of India New Delhi